Dampak Capital Structure, Profitability, Inflation, dan Interest Rates terhadap Nilai Perusahaan - Khoirunnisa, Rizka; Dewi, Anita Kusuma; Kurniawan, Umarudin (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This research aims to analyze and understand the impact of Capital Structure, Profitability, Inflation, and Interest Rates on Firm Value. The population of this research consists of companies in the energy sector listed on the Indonesia Stock Exchange from 2021 to 2023. This study is based on signaling theory. A total of data from 83 companies was selected using purposive sampling method. The data analysis techniques used are descriptive statistical analysis, classical assumption testing, and hypothesis testing with the help of SPSS version 27. The results show that: (1) Capital Structure has a positive effect on firm value, (2) Profitability has a positive effect on firm value, (3) Inflation does not affect firm value. (4) Interest Rates does not effect firm value.